2009
DOI: 10.1007/s12630-009-9169-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuous peripheral nerve blocks for postoperative analgesia in children: feasibility and side effects in a cohort study of 339 catheters

Abstract: Introduction Perioperative continuous peripheral nerve blocks (CPNB) are increasingly being used in children. Only one previous study has reported adverse events of CPNB in a high number of pediatric cases. We evaluated the indications, block efficacy, and adverse events related to CPNB in children. Methods All CPNBs that were performed in children for postoperative analgesia over a 5-year period at the Montpellier University Hospital in France were included in this study. The first bolus dose and the continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 31 publications
3
47
0
1
Order By: Relevance
“…5,6 Cohort analyses support this view and suggest a higher benefit-to-risks ratio for peripheral blocks. 5,19 One of the most important adverse effects of both central and peripheral blocks is motor block and sphincter functional dysfunction. No adverse effects or motor blocks were found in the caudal or pudendal groups postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Cohort analyses support this view and suggest a higher benefit-to-risks ratio for peripheral blocks. 5,19 One of the most important adverse effects of both central and peripheral blocks is motor block and sphincter functional dysfunction. No adverse effects or motor blocks were found in the caudal or pudendal groups postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Ganesh et al2 experienced leakage in five (2.3%) patients, and this was the cause of early removal in one of them. Other studies have demonstrated accidental catheter removal in 15%7 and 10.5%8 of patients. To help decrease the incidence of catheter leakage, we typically occlude the catheter insertion site with a small drop of Dermabond™ to seal the site.…”
Section: Discussionmentioning
confidence: 90%
“…Their potential benefits include earlier ambulation, improved outpatient pain management, fewer complications and reduced opioid-related side-effects 9 . Although the safety and efficacy of CNBs including outpatient use 10 has been reported in paediatric patients 8 , most reports pertain to their use for postoperative pain control 7,8,10,11 . There are limited reports on the use of this technique for other indications in children 12,13 , including the use of long-term CNB catheters for palliative pain control at the end of life 14 .…”
Section: Discussionmentioning
confidence: 99%